A new method of simulating volcanic eruption column formation and dispersion of ejected ash clouds. (29th November 2017) - Arenal, F. Espinosa; Avila, R.; Raza, S. S.
ABSTRACT: A new Eulerian−Lagrangian model is developed to predict the formation of eruption columns, and the long range transport and dispersion of volcanic ash clouds in the atmosphere. The model capability is tested by presenting the atmospheric dispersion of ash clouds released during two eruptions of the Popocatepetl volcano in Mexico. The atmospheric wind predictions were made by using the Eulerian regional atmospheric modelling system (RAMS), which is well tested over the Mexico region. Two Lagrangian models were also employed: (1) an eruption column formation model and (2) a Lagrangian stochastic deterministic (LSD) particle dispersion model. In a LSD model, the continuous plume is simulated by several puffs (clouds) successively released in the atmosphere. (1) The influence of the wind on the eruption column, (2) the transport and dispersion of the ash cloud and (3) the concentration of volcanic ash using a smoothed particle hydrodynamics technique are reported. This is thought to be a unique combination of mathematical prediction models and would be of interest to the broader scientific community. The formation of the eruption column is compared with ground observations, while the long range trajectory of the ash clouds is compared with images based on satellite data, qualitatively. In both cases the agreement within the observed and simulated plume shape was found to be satisfactory which indicated the suitability of the Eulerian wind prediction model (RAMS) in the region as well as that of Lagrangian models employed in the study. Abstract : A new Eulerian−Lagrangian model is developed to predict the long range transport and dispersion of volcanic ash clouds in the atmosphere as shown in the figure. A Eulerian regional atmospheric modelling system was used for wind field prediction and a Lagrangian stochastic particle model was used for turbulent dispersion. The model capability was tested by qualitatively comparing the simulated ash clouds with the satellite images of two eruptions of the Popocatepetl volcano in Mexico.